ANALISIS HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN CHANDRA SUPERSTORE TANJUNG KARANG BANDAR LAMPUNG - Ardansyah -; Ni Nengah Dwi Puspayani (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2017)
Every business in each business category is required to have sensitivity to any changes thatoccur and puts the orientation to customer satisfaction as a primary goal. Companies in givingsatisfaction to customers, must learn in advance the wishes and needs of consumers at the momentand will datangSetiap businesses in each business category is required to have sensitivity to anychanges that occur and puts the orientation to customer satisfaction as a primary goal. Companies ingiving satisfaction to customers, must learn in advance the wishes and needs, consumers today and inthe future.There are research results obtained by the effect of price on customer satisfaction ChandraSuperstore Tanjung Karang Bandar Lampung, There is the influence of service quality on customersatisfaction Chandra Superstore Tanjung Karang Bandar Lampung There is influence between priceand quality of service to customer satisfaction Chandra Superstore Tanjung Karang, Bandar Lampung.Suggestions that customer satisfaction can be increased should the price and quality of service that isalready good can be maintained and enhanced by Chandra Superstore employees Tanjung KarangBandar Lampung especially in giving a good idea of the quality Chandra Superstore to the family ..